Efficacy and Safety of Topical Calcipotriol and Betamethasone in Plantar keratoderma with Fissures (Journal of Dhaka National Medical College & Hospital, 2018)
Background: Fissured sole is a common problem in dermatology. A great number of people in our country have been suffering from plantar keratoderma which may lead to fissuring. Fissured sole is prevalent worldwide but is more common in third world countries, may be due to malnutrition, walking bare foot. No treatment available is a definitive cure. Topical calcipotriol and betamethasone valerate ointment is used in the treatment of plantar kertoderma with fissures.Objectives: To evaluate efficacy and safety of topical calcipotriol and betamethasone valerate ointment in the treatment of plantar keratoderma with fissures as well as to determine the response on histopathological types.Materials and methods: The clinical trial was done in the Department of Dermatology and Venereology, BSMMU, Dhaka, from January 2013 to December 2013. A total of 60 patients were included in the study which was randomly divided into two groups, each of which included 30 patients. Group A was given calcipotriol ointment at night and betamethasone velerate ointment in the morning for six weeks. Group B was given Vaseline for the same frequency and duration. Patients were clinically observed for the efficacy and side effects of the trial medicine after completion of therapy (after 6 weeks) and after 10 weeks. Baseline biopsy and histopathology, Skin scraping for fungus from the sole, random blood sugar and haemogram were done.Result: Among 60 studied cases, age range was from 10-69 years, with most commonly affected age group was 40-49 (26.7%). Both sexes were affected with female predominance (63.3%). People of middle class socio-economic condition are more susceptible. Histopathologically it was found that more common cause of plantar keratoderma with fissured sole was psoriasis 29 (48.3%). The therapeutic response of the study group after 6 weeks showed 06 (20.0%) patient respond good, 13 (43.3%) patient respond very good and 05 (16.7%) patient respond excellent. But 04 weeks after completion of treatment (at 10 weeks) 46.7% of study group (group A) and 86.7% of group B showed no response and 53.3% of group A and 13.3% of group B showed poor response. Side effect was minimal with only 04 (13.3%) patients had burning sensation.Conclusion: Topical calcipotriol and betamethasone velerate is effective and safe in planter keratoderma with fissures, but there is significant recurrence after discontinuation of treatment.J. Dhaka National Med. Coll. Hos. 2018; 24 (02): 27-31